1985
DOI: 10.1136/bmj.291.6492.383-a
|View full text |Cite
|
Sign up to set email alerts
|

Anxieties in adolescents about unemployment and war.

Abstract: Lead hazard in British stained glass workers Few studies have been undertaken into lead exposure among stained glass workers. In a recent survey of a studio in the United States Landrigan and his colleagues concluded that the blood lead concentrations were within acceptable limits for occupational exposure.' We have surveyed four stained glass workshops, the largest in Britain, and found that the potential for lead exposure is greater than previously recognised. All the workshops manufactured stained glass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…2. However, based on earlier research, we expected to find gender differences: Girls have been found to be more interested in future family and marriage compared to boys (Gillies, Elmwood. & Hawtin, 1985;Solantaus, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…2. However, based on earlier research, we expected to find gender differences: Girls have been found to be more interested in future family and marriage compared to boys (Gillies, Elmwood. & Hawtin, 1985;Solantaus, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…When one compares the findings of risk and resiliency-related research carried out in Ireland with that of commentators in the United States (US Department of Education, 1997) and in the UK (Donaldson, 1978;Gilles, Elwood, & Hawtin, 1985;Rutter;, one realises that Irish children are better off by a thousand fold in comparison to some of their international peers. Irish children are not shot dead on the streets by police or army hit squads as is reputed to be the case in Rio de Janeiro or experimented on by unscrupulous scientists, as was the case in other countries such as under the Nazi regime in the 1930s.…”
Section: Delimitations and Key Assumptionsmentioning
confidence: 93%
“…1 ' To these I would add economic diversification and conversion away from unhealthy production towards healthier products, and consumer pressure to achieve these.…”
Section: Miscellaneousmentioning
confidence: 99%
“…15 A number of alternative product development agencies have been formed by ex-members of the Combine and a National Network of Product Development Agencies has been formed. 1 ' Some of the products under development or in commercial production arising from this initiative are shown in Table 2. The Bristol study is the largest and most recent, and enjoys the widest support from academics, trade unionists and workers.…”
Section: Arms Conversion As a Public Health Issuementioning
confidence: 99%